Semantic query answering in digital repositories: Semantic Search v2 for DSpace. (1st January 2013) - Koutsomitropoulos, Dimitrios A.; Solomou, Georgia D.; Papatheodorou, Theodore S.
The added value the Semantic Web has to offer can find fertile ground in querying collections with rich metadata, such as ones often occurring in digital libraries and repositories. A relevant such effort is the semantic search service for the popular DSpace digital repository system. Semantic Search v2 introduces a structured query mechanism that makes query construction easier as well as several improvements in system design, performance and extensibility. Queries are targeted towards the dynamically created DSpace ontology, containing constructs that enable knowledge acquisition among available metadata. Both an empirical and a quantitative evaluation suggest that the system can bring semantic search closer to inexperienced users and make its benefits evident in the context of digital repositories, such as new querying dimensions, thus forming a paradigm production services can built upon.